Temperament and stress coping styles in bronchial asthma patients - Panek, Michał; Kuna, Piotr; Witusik, Andrzej; Wujcik, Radosław; Antczak, Adam; Pietras, Tadeusz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2016)
Introduction : Temperament, defined as the formal characteristics of behavior, is a personality trait which can influence the clinical presentation and course of bronchial asthma. It determines susceptibility to stress as well as stress coping styles. Aim: The aim of the study was to assess whether healthy subjects differ from bronchial asthma patients with regard to temperamental variables and stress coping styles, and whether these factors may also differentiate patients with severe asthma from those with the milder form. The study also assesses whether the results of flow volume curve analysis correlate with temperamental traits and stress coping styles. Material and methods : The study was conducted in a group of 65 asthma patients and 62 healthy controls. All underwent flow volume curve examination and psychological tests: Formal Characteristics of Behavior – Temperament Inventory (FCB-TI) and Coping in Stress Situations (CISS) questionnaire. Results : Bronchial asthma patients were characterized by a lower level of briskness (“agility”) than healthy subjects (13.35 ±4.48 vs. 14.97 ±3.98, p = 0.031). The remaining temperamental traits and stress coping styles did not differ between the groups. Additionally, the forced expiratory volume in 1 s (FEV1) value was found to correlate negatively with the intensity of the emotion-oriented stress coping style, whereas FEV1 and forced vital capacity (FVC) were found to positively correlate with briskness, emotional reactivity and endurance, while a negative correlation was found with activity. Conclusions : Briskness differentiates healthy subjects from bronchial asthma patients. The values obtained in FEV1 and FVC pulmonary function tests were also found to correlate with some temperamental variables.